Pengetahuan Orang Tua Berhubungan dengan Penanganan Hipertermi pada Balita di Desa Wajak Kabupaten Malang - Astutik, Vivin Yuni; Sutriyani, Titin (Yayasan Mandar Indonesia, 2025)
Hyperthermia in toddlers is a high-risk condition that requires prompt management by parents. High fever can cause shock, which if not treated immediately, may result in death. This study aims to identify the relationship between parental knowledge and the management of hyperthermia in toddlers in Wajak Village, Malang. This research employs a cross-sectional approach, with parental knowledge as the independent variable and hyperthermia management as the dependent variable. The population consisted of 41 mothers with toddlers. This quantitative study used a total sampling method and was conducted in Wajak Village, Malang Regency, from January to February 2023. Data analysis was performed using simple linear regression correlation tests. The results showed a significant relationship between parental knowledge and the management of hyperthermia in toddlers in Wajak Village, Malang Regency. It is recommended that healthcare workers and village authorities enhance counseling through educational media such as leaflets, videos, and training for posyandu cadres to improve parental knowledge, especially among mothers.